(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article tells about the new agrarian policy in the Republic of Uzbekistan, about new approaches to financing the developing agro-industrial complex. Timely state reforms and strategic planning in the field of attracting investments in the agrarian sector of the Republic.